Tingkat Kesulitan Belajar Siswa dalam Pembelajaran Geografi di Masa Pandemi dan Sesudah Pandemi - Wahyuni; La Harudu; Andrias; La Ode Nursalam (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
Online learning during the pandemic and after the Covid-19 pandemic, has a level of difficulty in learning Geography. This research aims to determine the level of student learning difficulties in learning Geography during the pandemic and after the Covid-19 pandemic. This research uses quantitative research and descriptive statistical analysis. The research results show that students experience learning difficulties that are influenced by internal and external factors. Internal factors include interest factors: students are less interested in participating in learning, and less active; Motivational factors: students lack motivation, perseverance, and learning knowledge. Meanwhile, in the post-pandemic period, it includes interest factors with no different causes; Motivational factors: students have the desire to learn, and students enjoy learning. External factors come from family factors; parents pay less attention to children's learning and provide support, for economic reasons; school factors: the relationship between students and teachers is not good, and learning methods are not good. Meanwhile, the post-pandemic period consisted of family factors: uncomfortable home atmosphere, economic reasons, and lack of support from parents; school factors: uncomfortable classroom atmosphere, and lack of facilities and infrastructure.